A A Systematic Literature Review: The Servant Leadership Supervision Model in Enhancing Teachers’ Organizational Citizenship Behavior in Indonesia - Puspitasari, Fantika Febry; Maimun, Agus; Amrullah, Abdul Malik Karim (Journal of Education Reseach and Evaluation, 2025)
In the context of education, the Organizational Citizenship Behavior (OCB) of educators has a significant impact on teaching quality, school climate, and student achievement. However, research on how supervision with a service leadership approach can improve educators' OCB in Indonesia is limited. The purpose of this study is to find an effective supervision model based on service leadership type to improve Organizational Citizenship Behavior (OCB) among teachers in Indonesia, especially at the junior high school level. This research used the Systematic Literature Review (SLR) method. The subjects involved in this study were relevant scientific publications, both in Indonesian and English, that focused on the context of educational institutions in Indonesia. The literature search was conducted through academic databases such as Google Scholar and Crossref on the Publish or Perish application. Inclusion and exclusion criteria were set to select studies that were most relevant to the research topic. Data from the selected studies were systematically analyzed to identify categories of supervision models that are effective in improving teachers' OCB in Indonesia. The results of this study show that there are several categories of supervision models based on service leadership types that are effective in improving teacher OCB in Indonesia, namely: (1) Supervision: Recognition and Reward as part of performance supervision, (2) Individual Development: Employee Development as the main focus in strengthening OCB, (3) Communication: Empathy and Engagement in effective communication between leaders and teachers, (4) Conflict Management: Service Leadership as mediation in handling conflict and facilitating harmonious resolution.